Patient assessment tutorials : a step-by-step procedures guide for the dental hygienist - Nield-Gehrig, Jill S. (Jill Shiffer).; Willmann, Donald E. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
'The ability to accurately assess patients is vital to the practice of Dental Hygiene--a complete and accurate assessment is the starting point to providing thorough patient care. Patient Assessment Tutorials takes you through the process of patient assessment, and provides you with information on both the actual physical assessment as well as effective patient communication. The highly visual, step-by-step style teaches you vital assessment processes quickly and thoroughly. Excellent features include detailed, full-color illustrations and photographs to visually guide you through procedures and techniques, case studies and personal accounts that bring the content to life, and more.'--Provided by publisher.
pt. 1. Communication techniques for assessment. 1. Communication skills or assessment : The communication process ; Communicating with patients -- 2. Making our words understandable : Roadblocks to effective communication ; Making health care words understandable ; Using the Internet to improve communication skills -- 3. Overcoming communication barriers : Language barriers ; Age barriers ; Vision and hearing barriers ; Speech barriers -- pt. 2. Assessment skills. 4. Medical history : The medical history assessment ; Informed consent and the medical history ; Conducting a medical history assessment ; Peak procedure -- 5. Ready references: medical history : Medical conditions and diseases ; Common prescription medications -- 6. Dental health history : Adult dental health history questionnaire ; Child dental health history questionnaire ; Peak procedure -- 7. Vital signs: temperature : Introduction to vital signs assessment ; Peak procedures -- 8. Vital signs: pulse and respiration : Peak procedure for pulse assessment ; Peak procedure for assessing respiration -- 9. Vital signs: blood pressure : Blood pressure assessment in the dental setting ; Equipment for blood pressure measurement ; Measurement and documentation of Korotkoff sounds ; Critical technique elements ; Peak procedures -- 10. Tobacco cessation counseling : Health effects of tobacco use ; Harmful properties of tobacco ; Why should dental health care providers intervene? ; Guidelines for tobacco cessation counseling ; Smoking cessation products ; Peak procedure: tobacco cessation -- 11. Soft tissue lesions : Learning to look at lesions ; Peak procedure: describing lesions ; Detection and prevention -- 12. Head and neck examination : Examination overview ; Methods for examination ; Peak procedure -- 13. Oral examination : Examination overview ; Peak procedure -- 14. Gingival description : Learning to look at the gingiva ; Peak procedure -- 15. Mixed dentition and occlusion : Sorting out a mixed
Includes bibliographical references and index.
Keywords: Diagnosis, Oral -- methods -- Programmed Instruction; Dental Hygienists -- Programmed Instruction; Dental Records -- Programmed Instruction